Customer Relationship Management pada Perusahaan Pelayaran Nasional di Indonesia - Gasing, Umar; Ricardianto, Prasadja; Pahala, Yosi; Tatiana, Yana; Handayani, Sri (Institut Transportasi dan Logistik Trisakti, 2023)
One of the companies in freight forwarding services in Indonesia is PT Pelayaran Lintas Harmoni. It provides custom clearance services, cargo shipments and goods delivery from abroad and domestic. Due to the pandemic, the company had lessen the goods distribution activities. In order to survive, the company should pay much more attention to the customer needs. This research aims to find out the direct and indirect effect of logistics service quality and customer relationship management through customers’ satisfaction to customers’ loyalty. The research used Path Analysis and Smart PLS as the analysis tool with a total sample of 105 respondents. The sample was taken from the customers directly related to the importer’s department. The results show that the study has a direct, indirect and significant influence on customers’ loyalty of the logistics service quality and customer relationship management by making the customers satisfied. It shows that the quality of logistics services not only measure the physical attributes but also focus more on how to approach the customers and find out about their needs.